Protocol to apply spike-in ChIP-seq to capture massive histone acetylation in human cells - Di Wu; Liguo Wang; Haojie Huang (STAR Protocols, 2021)
Summary: Inhibition of histone deacetylases causes rapid and robust acetylation of histones. In this case, histone acetylation is likely increased on nearly every nucleosome, and the per-cell DNA/chromatin yield in chromatin immunoprecipitation (ChIP) experiments is significantly increased. Spike-in controls are essential for normalizing ChIP sequencing (ChIP-seq) data to capture this massive effect. Here, we report a detailed protocol of H3K27-ac ChIP-seq in human cells with chromatin from an ancestral species as a spike-in control.For complete details on the use and execution of this protocol, please refer to Wu et al. (2021).